Employee Performance Assessment for Promotion with the Topsis Method in Senayan Apartments Jakarta - Sunarti, Sunarti (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Apartment Senayan Jakarta is a company engaged in rental services. Job promotion is carried out every year. Job promotion makes motivated employees work well and enthusiasm in self-development to improve the quality of performance. Performance evaluation as material for employee evaluation for promotion in Senayan Apartment Jakarta by utilizing the Technique for Order Preference method by Similarity of Ideal Solution (Topsis). This method can show evaluation ranking from highest to lowest by ranking alternatives in the form of employee data and dynamic criteria. The purpose of this study is the selection of quality employee performance for promotion based on the specified criteria. Based on the data sample used as many as 14 employees, the results of the assessment are based on rank, ie employees on behalf of Ridan get the first rank with a value of 0.50.